VD_OMNI CCST.2006.0002 vom 30. Mai 2006 - VD Tribunal cantonal (2006)
Commune de MORGES, VORUZ, GORRITE, GRIVEL, JACQUEMAI, JOMINI, PACCAUD, PITTET, AMSTEIN, KAESER, LABOUCHERE, ROSTAN, BOURQUI, CHAPALAY, DAÏNA, DEBLUË, FELLER, GOGNIAT, GOLAY, GRANGIER, GROGNUZ, KOHLI, DE HALLER, LEUBA, PAREAZ, PAYOT, DE PREUX, REICHEN, REYMOND, ROLAND, SURER, THIBAUD, Commune d'ARNEX | L'intérêt digne de protection de l'art. 9 al. 1er LJC peut être de pur fait.